Data security in ASEAN's digital economy: lessons from the Philippines - Enriquez, Jose Miguelito (2023)
Recent data breaches targeting Philippine government agencies have underscored the need to ensure a secure digital data environment. As ASEAN continues to lay the groundwork for its digital community and economy, the responsibility for data security must be shared by both domestic policymakers and relevant ASEAN mechanisms and frameworks.